Ionization cross sections of the Au L subshells by electron impact from the L3 threshold to 100 keV. (21st December 2017) - Barros, Suelen F; Vanin, Vito R; Maidana, Nora L; Martins, Marcos N; García-Alvarez, Juan A; Santos, Osvaldo C B; Rodrigues, Cleber L; Koskinas, Marina F; Fernández-Varea, José M
Abstract: We measured the cross sections for Au L α, L β, L γ, L ℓ and L η x-ray production by the impact of electrons with energies from the L3 threshold to 100 keV using a thin Au film whose mass thickness was determined by Rutherford Backscattering Spectrometry. The x-ray spectra were acquired with a Si drift detector, which allowed to separate the components of the L γ multiplet lines. The measured L α, L β, L γ 1, L γ 2, 3, 6, L γ 4, 4 ′, L γ 5, L ℓ and L η x-ray production cross sections were then employed to derive Au L1, L2 and L3 subshell ionization cross sections with relative uncertainties of 8%, 7% and 7%, respectively; these figures include the uncertainties in the atomic relaxation parameters. The correction for the increase in electron path length inside the Au film was estimated by means of Monte Carlo simulations. The experimental ionization cross sections are about 10% above the state-of-the-art distorted-wave calculations.